2017
DOI: 10.1002/cam4.1027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of distinct long noncoding RNA transcriptional fingerprints in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive and lethal malignancies with the worst prognosis. Recent studies have demonstrated that long noncoding RNAs (lncRNAs) play critical roles in tumorigenesis and cancer progression. However, the expression pattern and roles of lncRNAs in the development of PDAC remain unknown. Herein, we globally analyzed the lncRNA expression profile in human PDAC and non‐tumor tissues using four independent public microarray datasets from Gene Expression Omni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…For further in‐depth analysis, the lncRNA CASC9 , whose knockdown by three different methods was consistently associated with a loss of cell viability, was selected. The link of CASC9 to viability and proliferation was further supported by data from other tumor entities . We showed that the impact of CASC9 depletion was caused by a mixed phenotype including loss of proliferation and induction of apoptosis.…”
Section: Discussionsupporting
confidence: 66%
“…For further in‐depth analysis, the lncRNA CASC9 , whose knockdown by three different methods was consistently associated with a loss of cell viability, was selected. The link of CASC9 to viability and proliferation was further supported by data from other tumor entities . We showed that the impact of CASC9 depletion was caused by a mixed phenotype including loss of proliferation and induction of apoptosis.…”
Section: Discussionsupporting
confidence: 66%
“…Transcriptional fingerprint analysis in pancreatic ductal adenocarcinoma (PDAC) demonstrated that F11-AS1 is downregulated in PDAC tumor tissues and cell lines. These results suggest that dysregulated lncRNAs play important roles in PDAC development and progression [54]. A literature review revealed that the remaining prognostic DELs identified in the present study were not reported previously, and their function in HCC and other cancers needs to be further investigated and verified.…”
Section: Discussionmentioning
confidence: 81%
“…DNA tiling arrays contain oligonucleotide probes encompassing an entire length of a defined DNA regionto identify novel lncRNAs so that DNA tiling arrays are a major advantage to discover new lncRNA. Some companies developed their microarray chips to detect lncRNA such as Array star and Affymetrix with about 30,000 lncRNA expression panel assay [9] . RNA-seq is a very powerful technique to detect and quantify lncRNAs as Fig4B.…”
Section: Clinical Sample and Detectionmentioning
confidence: 99%